Innovation of Cilembu Sweet Potato-Based Chicken Nuggets as an Effort to Prevent Stunting - Aguslina Kirtishanti; Chatarina Yayuk Trisnawati; Sylvi Irawati; Jefman Efendi Marzuki (GUYUB: Journal of Community Engagement, 2025)
Stunting remains an important health issue in Duyung Village, Trawas Subdistrict, Mojokerto Regency. Cilembu sweet potatoes, which are nutrient-dense and widely available in the village, currently have low economic value. Processing these sweet potatoes into food products can enhance nutrient value, support stunting prevention, and improve their economic worth. To effectively and healthily utilize the local potential of Cilembu sweet potatoes, a training activity focused on preparing Cilembu-based chicken nuggets was conducted using the Participatory Action Research (PAR) method, which encompasses problem and needs identification, action planning, implementation, and reflection and sustainability. Fourteen participants were involved in the activity. The median score for perceived knowledge and skills in making Cilembu sweet potato-based chicken nuggets increased significantly after training compared with before training (3.0 vs 1.5, p = 0.006; 3.0 vs 1.0, p = 0.002). As many as 92.9% of participants reported the activity was beneficial and satisfying. Continuous monitoring and evaluation are necessary to ensure the continued production of Cilembu sweet potato-based chicken nuggets and to assess their long-term effects on the village community's economy and health